2019
DOI: 10.1002/btpr.2911
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up of a Type I secretion system in E. coli using a defined mineral medium

Abstract: Secretion of heterologous proteins into the culture supernatant in laboratory strains of Escherichia coli is possible by utilizing a Type I secretion system (T1SS). One prominent example for a T1SS is based on the hemolysin A toxin. With this system, heterologous protein secretion has already been achieved. However, no cultivations in a defined mineral medium and in stirred tank bioreactors have been described in literature up to now, hampering the broad applicability of the system. In this study, a mineral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…By variation of inducer concentration and time of induction, recombinant protein expression can be tuned and optimized ( Wandrey et al, 2016 ; Mühlmann et al, 2017 ). For Escherichia coli , monitoring of the oxygen transfer rate (OTR) or the scattered light signal was demonstrated to be a useful tool for optimization of recombinant protein production in small scale ( Ladner et al, 2017 ; Ihling et al, 2020 ). In addition, non-invasive online monitoring of the OTR in shake flasks combined with analysis of offline-determined culture parameters can be used for a detailed assessment of cultivation conditions and whole-cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…By variation of inducer concentration and time of induction, recombinant protein expression can be tuned and optimized ( Wandrey et al, 2016 ; Mühlmann et al, 2017 ). For Escherichia coli , monitoring of the oxygen transfer rate (OTR) or the scattered light signal was demonstrated to be a useful tool for optimization of recombinant protein production in small scale ( Ladner et al, 2017 ; Ihling et al, 2020 ). In addition, non-invasive online monitoring of the OTR in shake flasks combined with analysis of offline-determined culture parameters can be used for a detailed assessment of cultivation conditions and whole-cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial pre-culture supernatant samples were mixed with the Bradford reagent in cuvettes, and the absorbance was measured at 595 nm after allowing the reaction to proceed for 5 min at room temperature. The protein concentrations of the samples were determined using a standard curve and calculated using a linear regression equation obtained from the BSA standard curve [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was also revealed that by combining signal peptide and production rate screening, enhanced recombinant protein yields were obtained in the E. coli periplasm (Karyolaimos et al, 2019). One study established scale-up of a type I secretion system in E. coli using a defined mineral medium, paving the way for industrial application (Ihling et al, 2019). The industrially important strain engineering strategies utilized to increase both the quantity and quality of therapeutic products were discussed in another study (Castiñeiras et al, 2018).…”
Section: Escherichia Colimentioning
confidence: 99%